Pharmacotherapy, adverse drug reactions, and factors associated with clinical outcome in primary open-angle glaucoma - Anushree Dayanand; Sushma Muraraiah; S. Karthik Raja; Nishat Sultana Khayoom (Journal of Clinical Ophthalmology and Research)
Background: Glaucoma is a chronic, progressive optic neuropathy caused by a group of ocular conditions which lead to damage of the optic nerve with progressive diminution of vision. Medical management is currently the primary line of treatment in primary open-angle glaucoma (POAG). Aim: The aim of this study was to determine the pattern of pharmacotherapy and the adverse drug reactions (ADRs) and factors associated with clinical outcomes in patients with POAG. Materials and Methods: This cross-sectional study involved 100 patients diagnosed with POAG satisfying inclusion criteria. The demographic, clinical, and treatment data along with ADRs to antiglaucoma drugs were noted. Descriptive statistics and Chi-square test were used to analyze the data. Results: The most commonly prescribed antiglaucoma medications were timolol (76%) and latanoprost (31%). The most common fixed-dose combination (FDC) prescribed was timolol + brimonidine (20%). Thirty-seven percentage of the patients needed switch over from initial medications and 16% needed add-on therapy by the end of 1 year. The most common ADR was redness of the eye (30.5%). The target intraocular pressure (IOP) was achieved in 65% of the patients after 3 months of treatment. It was found that target IOP was associated with gender and residence. Conclusion: Timolol was the most commonly prescribed antiglaucoma medication though it reported the highest number of ADRs. Timolol + brimonidine is the most commonly prescribed FDC. The target IOP was achieved in two-thirds of the POAG patients.